Pengaruh Kompetensi Dan Komunikasi Organisasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening di KPP Pratama Banda Aceh - Audiva, Sarah; Imelda, Sarah; Syafii, Indra (Jurnal Ekonomi Bisnis Digital, 2022)
his research aims to find out the influence of competence and organizational communication on employee performance with job satisfaction as an intervening variable in KPP Pratama Banda Aceh. The population and sample used in the study totaled 108 employees. Sample withdrawal technique uses saturated samples. Data analysis techniques use path analysis with sobel tests. The results of this study showsthat competence has no effect on employee performance. Communication has an effect on employee performance. Job satisfaction has an effect on employee performance. Competence affects job satisfaction. Communication has an effect on job satisfaction. Competence affects employee performance intervenedby job satisfaction. Communication affects employee performanceintervenedby job satisfaction at KPP Pratama Banda Aceh.